Formulation and in vitro Evaluations of Paracetamol Orally Disintegrating Tablets - Azimuddin, Azmiera; Roslan, Mohamad Farhan; Teguh Widodo, Riyanto (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2023)
Orally disintegrating tablets are a solid dosage form compromising medicinal substances which disintegrate rapidly, generally within a matter of seconds, when placed on the tongue. In this study, paracetamol orally disintegrating tablets was formulated and evaluated. Direct compression was used to prepare 350 mg tablets of five formulations (F1- F5) by using a single punch manual tableting machine. Pre-formulation studies were performed on the powder mixture of each formulation to obtain information regarding their flow properties. The tablets from each formulation were also evaluated for weight uniformity, drug content uniformity, thickness, hardness, friability, disintegration and dissolution. The disintegration tests carried out revealed that tablets from F2 showed the shortest disintegration time of 32.67 ± 3.14 seconds followed by tablets from F5, F3, F4 and F1. However, the dissolution results illustrated that tablets from F5 have the best dissolution profile, releasing 84.70 ± 5.31% of drugs within 4 minutes. Hence the most optimized formulation of a paracetamol orally disintegrating tablet in this study.